2021
DOI: 10.1186/s12989-021-00419-w
|View full text |Cite
|
Sign up to set email alerts
|

Retained particle surface area dose drives inflammation in rat lungs following acute, subacute, and subchronic inhalation of nanomaterials

Abstract: Background An important aspect of nanomaterial (NM) risk assessment is establishing relationships between physicochemical properties and key events governing the toxicological pathway leading to adverse outcomes. The difficulty of NM grouping can be simplified if the most toxicologically relevant dose metric is used to assess the toxicological dose-response. Here, we thoroughly investigated the relationship between acute and chronic inflammation (based on polymorphonuclear neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…Toxicological studies have shown that LDSA correlates with negative health effects [ 26 ]. In our experimental conditions, LDSA values were lower than 50 µm 2 /cm 3 in all tests (see Figure 6 ) both at the NF and FF positions, and much lower than the peak value emitted by a burning candle (about 250 µm 2 /cm 3 ) and comparable with urban background sites in Los Angeles and in Cassino [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Toxicological studies have shown that LDSA correlates with negative health effects [ 26 ]. In our experimental conditions, LDSA values were lower than 50 µm 2 /cm 3 in all tests (see Figure 6 ) both at the NF and FF positions, and much lower than the peak value emitted by a burning candle (about 250 µm 2 /cm 3 ) and comparable with urban background sites in Los Angeles and in Cassino [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The parameters used for both models are reported in the Supporting Information. Whenever possible, the retained dose was preferred to the deposited dose as it has been shown to better correlate with the effects measured in the animal . Both in vitro and in vivo deposited/retained doses were normalized by the surface area of the cell culture well or the animal alveoli, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Toxicological evaluations of TiO 2 NMs are often performed using in vivo models such as mice and rats. Short and long term exposure to TiO 2 NMs via inhalation induced pulmonary inflammation, fibrosis and tumours [6,[13][14][15]. A significant increase in cytotoxicity, inflammation, oxidative stress, and DNA damage was observed in mice exposed to high doses (10 mg/kg [16] and ~4 mg/kg [17]) of TiO 2 NMs.…”
Section: Introductionmentioning
confidence: 99%